Latvia's Macroeconomic Options in the Medium Term: Fiscal and Monetary Challenges of EU Membership - Monga, Celestin (World Bank, Washington, D.C., 2013)
Latvia's experience over the past decade shows that economic growth and real convergence can no longer be assumed to be exogenously driven processes determined by given technological improvements and relatively higher factor returns. Instead, it is an endogenously driven process led by many variables, including policy variables. European Union membership clearly brings enormous economic benefits to Latvia. However, it also brings important challenges on the macroeconomic front, especially prior to the adoption of the euro. Substantial progress has been made toward fiscal consolidation since the mid-1990s but several risks remain. Given the facts that domestic demand remains buoyant and that Latvia will have to accommodate the expenditure commitments associated with NATO and EU membership while simultaneously aiming to fulfill the medium-term goal of a balanced budget, a more prudent fiscal policy should be the main short-term policy objective. The authorities should therefore reassess their current medium-term budget framework and strengthen their fiscal rules so that off-budget spending is eliminated and controls over spending ministries and local government finances are reinforced. They should also rethink any further tax reductions until a clear strategy is designed for compensating for projected losses in government revenues. Monetary policy can contribute to sustainable growth and job creation in Latvia in the medium and long term by providing an environment for price stability. It will have to be complemented by further microeconomic reforms and prudent wage developments aligned with productivity growth.